(untitled) (Research, Society and Development, 2022)
The temporomandibular disorder (TMD) consists of the functional alteration of the orofacial muscles, the temporomandibular joints, or both. Among the therapeutic options available for treating TMD, acupuncture appears as a relevant therapy to relieve pain and reduce the symptoms of clicking and discomfort of the temporomandibular joint. This study investigated the use of acupuncture as an auxiliary therapy in pain management in patients with TMD. A narrative review of the literature was performed using PubMed, Scielo, Bireme, LILACS, the American Association of Pain and the descriptor acupuncture, temporomandibular joint disorders, quality of life, dentistry, limited to the Portuguese, Spanish and English covering the publication period of 2012 to 2022. The highest prevalence rate of TMD is among women (about 80%) and the dysfunction appears after the age of 30. The main causes of TMD are related to behavioral, psychosocial and hormonal factors. Studies evaluating acupuncture for TMD treatment are limited. In contrast, significant short-term pain improvement was expressed in 26% of the articles. Taking into account that the disorder is mainly characterized by pain (algia), the reduction of this condition is of paramount importance.